Struggles in adolescence: a cross-group and multidimensional analysis on high school student depression and risk behaviors - Jessica K. Sun; Ayanda Chakawa; Daniel X. Zhang (International Journal of Adolescence and Youth)
This study examines the multifaceted relationships between depression and risk behaviours among high school students. It utilizes nearly 1.5 million samples to explore nine broad categories – driving unsafety, weapon-related behaviours, physical fights, suicidality, smoking, alcohol consumption, substance abuse, unhealthy eating, and physical inactivity – encompassing 50 individual components. Employing normalized association tests, logistic regressions, and bootstrapping methods, the analysis evaluates the strength and significance of the depression-risk behaviour association across demographic groups. This study also maps out the multidimensional pattern among intersectional subgroups, offering novel insights into how depression impacts diverse student populations. The results highlight the heterogeneity of depression’s effects across demographic subgroups, providing critical insights for tailoring mental health strategies. This research provides actionable findings informing educators, policymakers, and mental health practitioners, accentuating the need for targeted, data-driven interventions to mitigate risk behaviours and improve student well-being.